Introduction to modern statistical mechanics - Chandler, David, 1944- (Oxford University Press, 1987)
"[This] book contains concise explanations of such fundamentals as the connection between measurements and ensemble averages, discussions of equilibrium fluctuations and stability criteria, and the utility of Legendre transforms. It also explores many of the traditional elementary applications of statistical mechanics. Most importantly, it treats the principles and basic methods of time correlation functions (including the fluctuation-dissipation theorem and the Langevin equation), renormalization group theory, Monte Carlo simulations, and liquid structure."--Back cover.